PATIENT CLAIM FINANCING AT RSUP DR. KARIADI SEMARANG DURING THE COVID-19 PANDEMIC - Faik Agiwahyuanto, S.Kep.,M.Kes; Evina Widianawati; Widya Ratna Wulan; Via Ayusasmita; Deddy Setiadi (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
RSUP Dr. Kariadi Semarang sees both outpatients and inpatients to assess their health status and condition. Patient's health status and condition are classified into two groups: comorbid and co-incident. Patient claims are funded based on status and health conditions of comorbid and co-incident patients. The objectives this research is to know about the patient claim financing procedures of RSUP Dr. Kariadi Semarang during covid-19 pandemic. This research is descriptive qualitative using phenomenological. Primary data sources quotations were chosen using either purposeful sampling or criterion-based selection. The research informants are the primary informants. Informants are Hospital's first primary informant, the Coordinator of Coding Casemixes, and the second primary informant, the Nurse Coordinator of the Covid-19 Handling Room, as well as the first triangulation informant, the Head of the Medical Record Unit, and the second triangulation informant, the Head of the Covid-19 Handling Task Force. Interviews is methods for gathering data. Source triangulation is used for data triangulation. Data analysis using flow model of analysis and interactive analysis model. The result of this research are covid-19 with comorbidity or covid-19 with co-incident in patients because the guarantor is different, the case will be entered twice if it is a co-incident. If the condition is comorbid, the claim is handled separately. Previously, a claim was made for the covid-19 case, and if the covid-19 case was completed but the comorbidities persisted, the guarantor was changed from the Ministry of Health to BPJS Health. The conclusion is during the covid-19 pandemic, the procedures of RSUP Dr. Kariadi Semarang's patient claim financing process are two, such as the guarantor from the Ministry of Health and BPJS Health. Keywords: Patient claim, financing, process